Heterophonic Mayhem in the Archive: The Poetics, Surprises, and Disruptions of Animating the Arab Musical Diaspora - Rasmussen, Anne K.; Holton, Jared; Thomas, Anne Elise; Agha, Albert (MUSICultures, 2025)
This article describes the musical reinterpretation of Arab music, originally recorded one hundred years ago for a transnational industry of Arab, Arab American, and international record labels and recently released into the public domain. Inspired by colleagues at the Loeb Library at Harvard University, who highlight the recent American Music Modernization Act, the writers are university-based directors of Arab music ensembles who delve into this musical public domain to research, transcribe, study, practise and perform covers of these “golden oldies.” This article narrates the process and evaluates the work of re/animating musical archives.